A Novel Sushi-IL15-PD1 CAR-NK92 Cell Line With Enhanced and PD-L1 Targeted Cytotoxicity Against Pancreatic Cancer Cells - Xu, Da-Lai; He, Yuan-Qing; Xiao, Bin; Si, Yuan; Shi, Jian; Liu, Xue-Ang; Tian, Lei; Ren, Qian; Wu, Ya-Song; Zhu, Yi (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive and lethal malignancy with a limited response to current therapies. Novel and effective treatment is urgently needed. Herein, a chimeric antigen receptor (CAR)-NK92 cell line, with an interleukin (IL)-15Rα-sushi/IL-15 complex and a Programmed cell death-1(PD1) signal inverter was constructed and named SP (Sushi-IL15-PD1). We showed that CAR expression enabled SP cells to proliferate independently of IL-2 and became more resistant to nutrition starvation-induced apoptosis. Meanwhile, SP cells were more effective than NK92 in PDAC cell killing assays in vitro and in vivo, and there was a positive correlation between the killing capability of SP cells and PD-L1 expression in pancreatic cancer cells. Based on the synergistic and comprehensive effects of the special CAR structure, the adhesion, responsiveness, degranulation efficiency, targeted delivery of cytotoxic granule content, and cytotoxicity of SP cells were significantly stronger than those of NK92. In conclusion, the SP cell line is a promising adoptive immunotherapy cell line and has potential value as an adjuvant treatment for pancreatic cancer, especially in patients with high PD-L1 expression.